Isolasi dan Identifikasi Bakteri Endofit Rimpang Temulawak (Curcuma Xanthorrhiza Roxb) sebagai Penghasil Senyawa Antifungi terhadap Candida Albicans - Suci Tri Ramadhani; Ardi Mustakim (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Opportunistic fungal infections caused by Candida albicans pose increasing global health challenges, especially in immunocompromised patients. Resistance to conventional antifungal agents such as azoles and echinocandins has driven the search for alternative natural sources of antifungal compounds. This study reviews the isolation and identification of endophytic bacteria from Curcuma xanthorrhiza rhizomes and their potential to produce antifungal metabolites against C. albicans. Literature from the past ten years was analyzed, focusing on bacterial endophytes isolated from temulawak, their identification methods, and antifungal activities. Dominant endophytes such as Bacillus subtilis, B. amyloliquefaciens, and Pseudomonas fluorescens demonstrated significant inhibition of C. albicans growth, with inhibition zones ranging from 10 to 25 mm and minimum inhibitory concentrations (MIC) between 62.5 and 250 µg/mL. Antifungal activity is attributed to bioactive secondary metabolites, particularly lipopeptides produced by Bacillus species. Molecular identification via 16S rRNA sequencing confirms bacterial taxonomy, supporting further biotechnological exploration. This review highlights the promising potential of temulawak endophytic bacteria as a natural source for new antifungal agents to address drug resistance issues.